STRATEGI PENGUATAN LITERASI BERBAHASA ARAB BAGI SANTRI MILENIAL - Ahmad Syagif (Prodi PAI STIT Sunan Giri Bima, 2022)
Arabic literacy is a necessity that needs to be nurtured from an early age for students, especially among students. As millennials, the better literacy skills they have, the better their academic achievement will be so that they are more ready to answer the challenges of the times. This paper tries to dissect the various strategies that can be done to strengthen Arabic literacy for millennial students who are members of the MTSN 1 Kota Bima Boarding School Program. Through descriptive qualitative research with the case study method, it can be seen that the literacy strengthening program is carried out through habituation, development, and learning activities by combining the intracurricular curriculum and the non-curricular supplement curriculum. Arabic literacy can go hand in hand, reinforce each other with Al-Qur'an literacy and can be developed through digital literacy skills. The obstacle that is still being faced is the perception of the guardians of the students and the learning motivation of the students.